The quality of chief integrity officer and ethical climate on the level of ethics and integrity - Ishak, Ismail; Hasnah, Haron; Shamsudin, Norazidah (2019)
The effectiveness in implementing ethics and integrity is very important to reduce the ethical scandals such as corruption, bribery, fraud, governance inefficiency and poor internal control. Based on the statistics reported by the Malaysian Anti-Corruption Commission (MACC), it shows that civil servants are the most involved group in the ethical scandals starting from the top management until the lower staff in the public-sector organization. The objective of this study is to investigate the relationship between the three dimensions quality of the Chief Integrity Officer (independence, competence and work performance) and ethical climate with the level of ethics and integrity in Malaysian public-sector organization. Out of 128 questionnaires that were emailed to the CIOs in the Federal level, only 83 questionnaires were received and usable. Multiple regression was used to test the hypotheses of this study. The results of this study showed that the two dimensions quality of CIO (competence and work performance) and ethical climate have a positive and significant relationship with the level of ethics and integrity. On the other hand, the level of ethics and integrity was found to have a positive and significant relationship on organizational commitment. Thus, this study suggests that a higher CIO quality i.e. competence, work performance and ethical climate, will be able to enhance the level of ethics and integrity of the public sector in Malaysia. This study showed that the government efforts in implementing the national integrity agenda was fruitful because the level of integrity in the Malaysian public sector was at 73%. To increase the competency level of the CIO, it is highly advisable for them to enrol in more professional courses related to ethics and integrity. CIOs should also perform their roles such as coordinate and monitor programs and also report any breaches of integrity without fear or favour. To increase or improve existing ethical climate, the organization should establish clear policies, guidelines and conducts on ethics and integrity to all employees in the government ministries, department and statutory body in the public sectors.